The photo-monologue: critical device and activist practice. Issue 5 (20th October 2022) - Gil-Glazer, Ya'ara
Abstract : This article defines the photo-monologue : a combination of documentary portraits of subjects in a state of marginalisation, silencing, discrimination, or victimhood with their own verbal reflections. It describes and discusses the phenomenology of the photo-monologue as a critical rhetorical device as well as humanistic political practice. In addition, it addresses how the dialogic potential of photo-monologues is realised under certain conditions but less so in others. The first section defines and establishes the photo-monologue as a critical device of visual culture, including its history and its ethical and aesthetical aspects. The second examines its activist potential by discussing its arenas of display and dialogue. In addition, it proposes the photo-monologue as a practice in visual education for activism – where its dialogic potential may be realised most productively – and offers examples for this potential as applied in student projects.